Analisis Bahasa Indonesia dalam Kasus Pencemaran Nama Baik di Media Sosial - Dali, Meilina Widya; Putri, Nurul Alifa; Adam, Nur Ain; Masia, Ririn; Dini, Natasya Roi; Paputungan, Firgita; Hasan, Moh. Valken; Lamady, Rahmat Ghazi Al-gifari; Pelu, Muhammad Rendi; Husain, Mohamad Zaid Farel; Sidak, Khaliqin Nur; Hogi, Suleman; Mahmud, Khairuzzad F. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research analyzes the role of Indonesian in cases of defamation on social media through case studies handled by the Gorontalo Regional Police's special criminal investigation directorate. Using qualitative methods with semi-structured interview techniques, this research explores how the use of satire, irony and sarcasm contributes to defamation in the digital space. The research results show that indirect language styles function as a disguised medium of pollution, allowing the perpetrator to attack the victim's reputation while passing it off as humor or a casual opinion. The findings reveal the important role of forensic linguistic experts in analyzing the implied meaning, sociolinguistic context, and communicative intention of mixed language utterances used by perpetrators. The research also identified a low level of awareness of social media users regarding the legal consequences of inappropriate language use, especially regarding Article 27a in conjunction with Article 45 paragraph (4) UU IT and Articles 310, 311 of the Criminal Code. This study recommends the need for digital literacy education and legal understanding for the public to prevent abuse of freedom of expression on social media which can tarnish the honor of other people.